Plan integration for ecological resilience: examining factors associated with wetland alteration - Yu, S; Newman, G; Berke, P; Li, X (SAGE Publications, 2023)
A community’s resilience is strongly influenced by the growth management guidance provided by its network of plans. Wetland loss has been shown to amplify flood damage. This study explores the relationship between plan integration and wetland alteration, comparing the findings from Fort Lauderdale, Florida, and League City, Texas. Combining spatial analytics, a Plan Integration for Resilience Scorecard™ evaluation, and correlational statistics, we find that wetland loss is significantly associated with plan integration and development patterns and is less acute in League City than Fort Lauderdale. Integrating wetland protection policies throughout a network of plans helps build resilience to flood hazards.